Sensitivity, specificity and diagnostic accuracy of novices integrating lung ultrasound into the care of breathless older patients. Issue 4 (November 2015) - Baker, Kylie; Soong, Luke; Harding, Timothy; Wain, Amy; Cheah, Jon; Mitchell, Geoffrey; Brierley, Stephen
Abstract: Background: Lung ultrasound is frequently used to identify pulmonary oedema, using the 'B line' artefact. A small study in 2011 suggested that novice sonologists had a potential diagnostic accuracy of 85%, when performing the test without reference to other patient information. Aim: We aimed to test the overall diagnostic accuracy of novice clinician sonologists incorporating the 2011 protocol into routine assessment of the patient. Method: A prospective convenience sample of breathless older patients presenting to ED received an 8‐view lung scan early in management. Initial ED diagnoses, utilising all information including ultrasound result, were compared against the opinion of a medical expert auditing the patient records after discharge from hospital. Results: The cohort of five novices scanned 63 cases, from which eleven were excluded. Novices using ultrasound differentiated between pulmonary oedema and other causes of breathlessness with a sensitivity of 71% (95%CI 44 to 87), Specificity of 91% (76 to 98), a diagnostic accuracy of 85% (72 to 92), a positive LR of 8.2 (2.7 to 25) and a negative LR of 0.32 (0.15 to 0.68). Discussion: The diagnostic accuracy of emergency department clinicians incorporating novice lung ultrasound into the investigation of breathlessness is consistent with the diagnostic accuracy of scanning performed in parallel to patient care, and is likely to be an improvement on current estimates of conventional ED diagnostic strategies. Clinicians should not be afraid that their learning curve would disadvantage the patient.